Characterization of the 26S Proteasome S7 Subunit Gene and Its Expression during Regeneration in Apostichopus japonicus. Issue 2 (April 2015) - Qin, Yanjie; Zhao, Xiangji; Li, Xia; Wang, Yanfeng; Liu, Yang
Abstract The 26S proteasome, which includes 20S core and 19S regulatory particles, plays an important role in removing harmful and/or unnecessary proteins. In this study, we cloned a 2443‐bp full‐length cDNA sequence of the S7 subunit of 19S from the sea cucumber Apostichopus japonicus, including a 70‐bp 5′‐untranslated region (UTR) and 1070‐bp 3′‐UTR coding for a theoretical 435 amino acid protein. Sequence analysis showed that S7 belongs to the ATPases associated with a wide variety of cellular activities (AAA+) superfamily. S7 was widely expressed in different tissues as determined by real‐time quantitative polymerase chain reaction, and its expression was gradually upregulated in the regenerating body wall. Combined with histological observations, our results suggest that the S7 subunit or the 26S proteasome assembled based on S7 may be associated with the regulation of cell migration and cell cycle during body wall regeneration in A. japonicus.